(untitled) (Pedagogy of Higher and Secondary Education, 2012)
Havryshchak I. I. Pedagogical aspects in the scientific activity of Immanuel Kant The article investigates pedagogical activity of a famous German philosopher I. Kant, special attention is paid to the treatise «On Pedagogy». The conceptual provisions of the pedagogical foundations of the work were singled out; the analysis of teaching of the German philosopher was made.